2023
DOI: 10.3390/electronics12214553
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Domain Facial Expression Recognition through Reliable Global–Local Representation Learning and Dynamic Label Weighting

Yuefang Gao,
Yiteng Cai,
Xuanming Bi
et al.

Abstract: Cross-Domain Facial Expression Recognition (CD-FER) aims to develop a facial expression recognition model that can be trained in one domain and deliver consistent performance in another. CD-FER poses a significant challenges due to changes in marginal and class distributions between source and target domains. Existing methods primarily emphasize achieving domain-invariant features through global feature adaptation, often neglecting the potential benefits of transferable local features across different domains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This experiment demonstrated that students based their answers on discerning distinctive areas in the two bodies, mirroring the functionality of the LFP algorithm. It identifies distinguishing areas in images for subsequent utilization in machine learning [51], [52], [53].…”
Section: Learning Focal Point (Lfp) Algorithmmentioning
confidence: 99%
“…This experiment demonstrated that students based their answers on discerning distinctive areas in the two bodies, mirroring the functionality of the LFP algorithm. It identifies distinguishing areas in images for subsequent utilization in machine learning [51], [52], [53].…”
Section: Learning Focal Point (Lfp) Algorithmmentioning
confidence: 99%
“…Hence, it is evident that CNN models are highly beneficial for facial expression recognition tasks. Gao et al [11] presented cross-domain facial expression recognition (CD-FER). CD-FER integrates features across domains and incorporates dynamic label weighting.…”
Section: Related Workmentioning
confidence: 99%